Immunoendocrine Interactions during HIV-TB Coinfection: Implications for the Design of New Adjuvant Therapies - Suárez, Guadalupe Verónica (2015)
Worldwide, around 14 million individuals are coinfected with both tuberculosis (TB) and human immunodeficiency virus (HIV). In coinfected individuals, both pathogens weaken immunological system synergistically through mechanisms that are not fully understood. During both HIV and TB infections, there is a chronic state of inflammation associated to dramatic changes in immune cytokine and endocrine hormone levels. Despite this, the relevance of immunoendocrine interaction on both the orchestration of an effective immune response against both pathogens and the control of the chronic inflammation induced during HIV, TB, or both infections is still controversial. The present study reviews immunoendocrine interactions occurring during HIV and TB infections. We also expose our own findings on immunoendocrine cross talk in HIV-TB coinfection. Finally, we evaluate the use of adrenal hormones and their derivatives in immune-therapy and discuss the use of some of these compounds like the adjuvant for the prevention and treatment of TB in HIV patients.